Issues determining direct airways hyperresponsiveness in mice - Lundblad, Lennart K. (Frontiers in Physiology, 2012)
Airways hyperresponsiveness (AHR) is frequently a primary outcome in mouse models of asthma. There are, however, a number of variables that may affect the outcome of such measurements and the interpretation of the results. This article highlights issues that should be in mind when designing experiments using AHR as an outcome by reviewing techniques commonly used to assess AHR (un-restrained plethysmography and respiratory input impedance using forced oscillations), discussing the relationship between structure and function and, then exploring how the localization of AHR evolves over time, how the airway epithelium may affect the kinetics of methacholine induced AHR and finally how lung volume and positive end expiratory pressure (PEEP) can be used as tools assessing respiratory mechanics.